Upaya Promosi dan Pencegahan Kanker Payudara Menggunakan Whatsapp Messenger - Lasari, Hadrianti; Amalia, Momen; Sarmila, Sarmila (HIGEIA (Journal of Public Health Research and Development), 2021)
WHO said that around 70% of cancer deaths occurred in low and middle income countries and 9,6 million people worldwide died of cancer in 2018. In fact, 30-50% of cancer incidents can be prevented. The target of this study was the family of breast cancer patients who are undergoing outpatient treatment at Wahidin Sudirohusodo Hospital, Makassar City. This research was conducted from May 1, 2019 to October 30, 2019 and was a pre-experimental, one group pre and posttest and focuses on respondents who have a relative relationship with breast cancer patients. The results of the Wilcoxon signed rank test statistical test obtained p = 0,001 (p <0,05) which indicates a significant difference in the mean knowledge of respondents, before and after prevention promotion (20,37 to 23,80). So it can be concluded that there is a difference in knowledge before and after the promotion of breast cancer prevention via WhatsApp Messenger. Keywords: WhatsApp Messenger, Breast Cancer, Health Promotion